Tradition and Modernity: A Binary reading of Tess Onwueme’s the Broken Calabash - Emmanuel Tsadu Gana (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
The issue of culture, tradition, and its unassailable conflict with modernity in certain parts of Africa, as obvious in several communities in Nigeria, is a challenge that affects our social development today. As it is often echoed; “it’s a man’s world”, most times women fall victim of these long-held traditions that have over time become canons we hold dear. The glib dispositions of these practices situate patriarchy at the epicenter of societal construction and places women on us, the fringes, mostly becoming unwilling casualties of unfriendly traditions. Thus, this paper examines how tradition and its attendant problems impede on the social standing and general development of the woman in society using Tess Osonye Onwueme’s play ‘The Broken Calabash”. Using the thematic content analysis approach the paper explored the potential conflict between tradition and modernity, the paper interrogates Broken Calabash as a reflection of women’s subjugation by obsolete cultural traditions, presenting alongside this, the consequences of social exclusion and the denial of rights experienced by women. The paper concludes that the dramatic experience presented by Tess Osonye Onwueme reveals the intricate relations between tradition and modernity as a potent means for the reading and understanding of texts depicting gender relations.